Diretrizes de relacionamento para estruturação de contratos na cadeia de suprimentos: uma análise a partir do pensamento sistêmico - Stefano, Letícia da Silva (Universidade do Vale do Rio dos Sinos, 2023)
The complications of modern supply chains are compounded by a variety of factors, such as lack of transparency, continuity, stockouts or excesses, delivery delays, information disruption, and outages. In addition, there is more and more diverse competition every day, along with the increasing advancement of communication technology, making companies need to effectively develop their supply chain channels and, in this way, create connection and establish partnerships between the links. The study aims to analyze which opportunities for improvement can be identified when systematically evaluating the relationship guidelines for structuring contracts with suppliers in a supply chain of a company that distributes indirect supplies. These opportunities were understood from a case study and with the use of Systems Thinking. As a result, the problems identified in the supply relationships in the studied supply chain are evident, such as ruptures, difficulties in fulfilling agreements, suppliers with low capacity, lack of partnership relationships, inefficient planning, lack of contractual relationships, lack of understanding of demand forecasting and lack of safe processes efficiently. Finally, this research suggested from the literature, guidelines to solve supply chain supply problems.
Keywords: Cadeia de suprimentos; Contratos; Diretrizes; Relacionamentos; Pensamento sistêmico; Supply chain; Contract; Guidelines; Relationships; Systems thinking; ACCNPQ::Engenharias::Engenharia de Produção